C. S. Peirce’s Semiotic and Mathematical Conception of Economics - Wible, James (Recherches sémiotiques / Semiotic Inquiry, 2020)
C. S. Peirce had a keen interest in the most mathematical economics of his era. We know that Peirce read and wrote about the mathematical economics of Cournot and Jevons and at least mentions the names of Ricardo, Marshall, and Walras. Peirce also provided a mathematical, optimizing model of the insurance firm as his most elaborate example of pragmatism in the Harvard Lectures of 1903. What is significant is that Peirce chose economic examples to illustrate what is really a semiotic and mathematical conception of pragmatism. Diagrams and semiotics play a central role in Peirce’s philosophy of mathematics. Just a few years ago, Carsten Herrmann-Pillath authored a long treatise on evolutionary economics with Peirce’s semiotics as a central aspect of that work. Additionally, Herrmann-Pillath makes significant use of diagrams and equations from various scientific disciplines. Diagrams are a central feature of Herrmann-Pillath’s treatise giving it something of a Peircean, qualitative mathematical character. These similarities and differences between Peirce and Herrmann-Pillath on semiotics, economics, mathematics, and evolutionary processes are quite novel and thus of intrinsic interest.